The Diversity Barometer 2005-2022: time series data on attitudes towards ethnic diversity and immigration among the Swedish population. - Ahmadi, Fereshteh; Munobwa, Jimmy Stephen; Mella, Orlando (University of Gävle, 2025)
This dataset was generated through the Diversity Barometer, a study tracking attitudes towards ethnic diversity and immigration in Sweden since 2005. The data were collected annually between 2005 and 2014, and biennially thereafter. Unweighted samples, consisting of adults aged between 18 and 75 years were used. The data can be managed and analyzed in the statistical program SPSS. The dataset includes the following variable categories:
1. Respondent descriptives
2. Interaction with persons with foreign background at school, work and in the neighborhood.
3. Cultural rights for persons with foreign background.
4. Social rights for persons with foreign background.
5. Immigration as beneficial to the Swedish society.
6. Immigration as a threat to the Swedish society.
7. Attitudes towards Swedish immigration policies.
8. Immigrants are exploited in the Swedish labor market.
9. Interest in interacting with immigrants and learning foreign cultures.
10. Attitudes towards religion in general, and Islam in particular.
11. Willingness to live in the same neighborhood as immigrants.
12. Immigrant-neighborhoods are problem neighborhoods.

Detta dataset genererades genom Mångfaldsbarometern, en studie av attityder till etnisk mångfald och invandring i Sverige sedan 2005. Data samlades in årligen mellan 2005 och 2014, och vartannat år därefter. Vuxna mellan 18 och 75 år deltog i studien. Urvalens resultat redovisades ovägt. Data kan hanteras och analyseras i SPSS. Datasetet innehåller följande variabelkategorier:
1. Beskrivning av respondenterna.
2. Umgänge med personer med utländsk bakgrund i skolan och arbetsliv.
3. Kulturella rättigheter för personer med utländsk bakgrund.
4. Sociala rättigheter för personer med utländsk bakgrund.
5. Invandring som gynnsam för det svenska samhället.
6. Invandring som ett hot mot det svenska samhället.
7. Attityder till svensk invandringspolitik.
8. Invandrare utnyttjas på den svenska arbetsmarknaden.
9. Intresse av att interagera med invandrare och lära sig främmande kulturer.
10. Attityder till religion i allmänhet och islam i synnerhet.
11. Vilja att bo i samma bostadsområdet som invandrare.
12. Invandrartät är problemområde.
Mångfaldsbarometern 2005-2022: tidsseriedata om attityder till etnisk mångfald och invandring bland befolkningen i Sverige.
Keywords: MIGRATION (HUMAN); MIGRATION; IMMIGRANTS; INVANDRARE; IMMIGRATION; IMMIGRATION; ETHNIC GROUPS; ETNISKA GRUPPER; MIGRANTS; MIGRANTER; Sociology (Excluding Social Work, Social Anthropology, Demography and Criminology); Sociologi (exklusive socialt arbete, socialantropologi, demografi och kriminologi); International Migration and Ethnic Relations (IMER); Internationell migration och etniska relationer